IMPLEMENTASI PEMBELAJARAN KONSTRUKTIVIS UNTUK MENGEMBANGKAN AKTIVITAS SERTA PRESTASI PESERTA DIDIK - Nabila Zuhairya; Muhammad Faiz; Fauziah Nasution (CV. ADIBA ASIHA AMIRA, 2023)
The principle view that is often adhered to by constructivism, students actively build knowledge, the pressure in the learning procedure is on students, teaching is supporting students, the learning procedure is more concerned with procedures than the final result. The curriculum emphasizes the involvement of students and educators as mentors. So it's not other people's experiences that are abstracted and compiled in the form of textbooks, but direct experience from oneself. Based on the description above, to develop learning achievement and active learning, the usual learning method used is the constructivist learning cycle method. This type of research is library research. The results of this study are that students must build this knowledge and give meaning through real experiences. The purpose of this learning cycle learning method is to give freedom to students to think critically and scientifically and to test the truth of various hypotheses by gathering information from test scores. Then students interpret, analyze, and finally draw conclusions that are expected to develop student performance. In addition, in the learning cycle, students actively interact with ideas and peers during the research phase. As a result of this hands-on learning, students can better understand the design and develop student learning.